Until dignity becomes customary archiving the #28A strike in Colombia (2025)
ABSTRACT: The purpose of this paper is to document the creation of the Archivo del Paro #28A, a digital archive created in Colombia as a result of the social mobilizations that took place in 2021. To this end, we situate the cycle of protests that has been referred to as “social outburst” in a context of economic, political, and social crisis deepened by the effects of unequal management of the COVID-19 pandemic, but also in a context of political opening following the peace agreements between the State and the Revolutionary Armed Forces of Colombia—People’s Army (FARC-EP) in 2016. In this context, we argue that the social outburst of 2021 constituted a historical milestone in terms of democratic political participation and, consequently, we respond to the ethical and political duty of archiving it. We then show that the project for creating the Archivo del Paro #28A is inspired by other initiatives that have taken place in the international arena. Finally, we describe the process of creating the archive through the campaign “Hacer eterno lo efímero” [Making the ephemeral last forever], which framed the processes of gathering, classification, valuation, and dissemination of the collected documents as a strategy to achieve a broad diversity of voices.